Alternative electrification pathways for light-duty vehicles in the European transport sector. (October 2021) - Rottoli, Marianna; Dirnaichner, Alois; Pietzcker, Robert; Schreyer, Felix; Luderer, Gunnar
Highlights: Electrification is an attractive option to reduce CO2 emissions from transport. Alternative electrification options differ in terms of impact on the energy system. Indirect electrification might result in a critical burden on the supply sector. Policies addressing consumer preferences are crucial to trigger mobility shift. Abstract: There is a wide consensus that a fundamental technology shift within the light duty vehicles (LDVs) sector is necessary to achieve the emissions reductions required for the Paris Agreement's targets, but substantial controversy prevails about the most suitable strategy. While some decision makers favor a transition to battery electric vehicles, others advocate for fuel cell vehicles and e-fuels. These strategies differ markedly in terms of consumer acceptance and implications for the energy system. We explore a range of electrification pathways in Europe until 2050. Direct electrification leads to a strong reduction in direct CO2 emissions of LDVs, with electric vehicles reaching 90% of sales in 2050. Indirect electrification places substantially higher pressure on the supply sector, with almost double the primary energy demand relative to direct electricity use. In addition, the implementation of complementary policies addressing perceived inconvenience markups for alternative mobility is crucial to initiate the mobility transformation.